Android Based Inventory Stock Design Case Study On The North Jakarta Transportation Service Subject - Rizk, Muhamad; Tjahjono, Budi (International Journal of Science, Technology & Management, 2024)
Study This aim For visualize design general Android- based Inventory Stock system for the North Jakarta Transportation Sub – Department. Referring to Law Number 1 of 2004 concerning state treasury , goods or assets belonging to the state/ region in is all purchased items _ or obtained on burden Budget State/Regional Revenue and Expenditure (APBN/D) or originate from acquisition other valid ones , or items obtained _ based on decision powerful court _ law fixed ( provisions of Article 2 paragraph (2) of the Regulation Government Number 27 of 2014). Analysis the need will used in do development of "Android Based Inventory Stock Design Case Study On The North Jakarta Transportation Service Sub". Planning application , at stage This done making structure navigation , UML diagrams (use case diagrams, activity diagrams and class diagrams) for use make it easier stage planning to features that will made on the website and also the design appearance for the UI (User Interface) website version using Prototype High Fidelity (Figma). Planning system mean For something method after assessment from movement development , stage preparation For development or creation of application programs . With hope the system will made later can become solution on problems that exist in the North Jakarta Transportation Sub-dept. The Android- based Inventory Stock application provides solution to problem human error in recording inventory Manually. With automated and structured systems , risks _ error write , loss sheet paper , and errors calculation can minimized in a way significant . With connected system _ in a way direct with inventory database , information stock goods can accessed with fast and accurate , enabling takers _ decision For Act in a way more appropriate time . Application This give convenience in tracking inventory , even moment happen error or lost goods . Facility integrated tracking_simplify the process of searching and recovering accurate inventory data.